Cost-allocation methods for commuter, intercity, and freight rail operations on shared-use rail systems and corridors. - National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program; AERCOM Consult, Inc. (Washington, D.C. Transportation Research Board, 2007)
"This digest presents the results of NCHRP Project 20-65 (Task 12), 'Cost-allocation methods for commuter, intercity, and freight rail operations on shared-use rail systems and corridors.' The research was conducted by AERCOM Consult, Inc."--p. 1.
At head of document: National Cooperative Highway Research Program.
"February 2007."
Includes bibliographical references.
Also available online.
Keywords: Local transit -- Research; Railroads -- Commuting traffic; Transportation -- Planning; Railroads -- Management; Freight and freightage; Shared services (Management) -- Transportation